Improving the Students’ Ability in Reading Comprehension by Using Cooperative Integrated Reading Composition - Rohdearni Wati Sipayung (Budapest International Research and Critics University, 2019)
This research objective is to find out the student’s ability in reading comprehension by using CIRC. The population was the first grade students of SMP Swasta Cinta Rakyat 1 Melanthon Siregar Pematangsiantar.The research design was used classroom action research. To collect the data, the researcher uses test that consist of pre test and post test that is formed of multiple choice. In analyzing the data the researcher uses theory from Harris, A. J (1984) and Arikunto, S (2007). Based on analyzing the data, the researcher found that mean score of the students in pre-test is 40,66 and mean score from post test is 73,33. From the score in pre test and post test, the researcher can seen the significant improvement score of the students. Based on the result of the research, the researcher can suggest that the CIRC method is the effective method to teach reading especially in reading comprehension a text.